Prevalence and Risk Factors of Traumatic Dental Injuries among Conflict-Affected Schoolchildren in Syria (2023–2024) - Lana Alshayeb; Mohammed Nabil Al-Shiekh; Mayssoon Dashash (Journal of Epidemiology and Global Health)
Abstract Aim The prevalence of traumatic dental injuries (TDIs) and their contributing factors among Syrian children has not been explored in any previous epidemiological studies since the onset of the crisis. This study aimed to assess the prevalence of TDIs and their associated characteristics among schoolchildren aged 9 to 12 in Damascus, Syria. Materials and Methods We conducted this cross-sectional study from 2023 to 2024, collecting sociodemographic data and performing dental examinations, and the presence of TDIs, which were classified according to the World Health Organization’s guidelines. We recorded Screen time and categorized it into two groups. We measured Overjet in millimeters, and the statistical significance was set at P < 0.05. Results We identified TDIs in 17.6% of children, with uncomplicated crown fractures being the most common. Falls were the leading cause, and the home was the most frequent injury location. Significant risk factors included age, gender, socioeconomic status, screen time, Body Mass Index, and overjet. Males had twice the risk of TDIs compared to females (OR = 2.104, 95% CI: 1.399–3.165), and children from lower socioeconomic backgrounds had a 2.29 times higher risk (OR = 2.299, 95% CI: 1.364–3.877). Conclusion This study found that a significant proportion (17.6%) of Syrian children experienced TDIs, highlighting the urgent need for preventive programs and improved dental care for Syrian children affected by TDIs. Clinical Relevance Early identification of children at higher risk, prompt management of dental trauma, and educational initiatives for parents and educators are essential. Schools, as primary injury sites, should adopt safety measures, while dentists should engage in community outreach to enhance awareness, early diagnosis, and intervention.